Community stories of resilience building in ASEAN strengthening community resilience through peer-to-peer learning. (Oxfam, 2017)
Asia is vulnerable to more frequent and severe disasters due to the rapid rise of natural hazards, extreme weather events, and the impacts of climate change. ASEAN’s Declaration on Institutionalizing the Resilience of ASEAN and its Communities and Peoples to Disasters and Climate Change recognizes this, and its vision of resilience sets out to achieve ‘a more resilient future by reducing existing disaster and climate-related risks, preventing the generation of new risks, and adapting to a changing climate through the implementation of economic, social, cultural, physical, and environmental measures which address exposure and vulnerability, and thus strengthen resilience.’